2016
DOI: 10.1177/1359105315604379
|View full text |Cite
|
Sign up to set email alerts
|

Discerning the impact of personal and situational variables in risk perception of coronary heart disease

Abstract: Research into how people perceive risk has highlighted the interaction between the available information and personal variables and their impact on judgement. This study sought to identify demographic and health variables that influenced risk and the influence of individual risk assessment, dispositional optimism and negative affect on judgement. A total of 476 participants were asked to make risks judgements of 24 vignettes depicting hypothetical risk scenarios. The findings showed that while people are able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…The truthfulness and trustworthiness of our qualitative findings from CHD participants with their discussion of first‐hand and detailed experiences are also verified by the previous studies. Risk perception, which refers to patients’ evaluation of their probability of dangerous events and the harm of the possible event in our study, was reported to enable patients to better understand the importance of reducing their risk for future cardiac events (Figueiras et al, 2017). Consequently, risk perception assists them in engaging in risk‐reducing intentions and behaviours.…”
Section: Discussionmentioning
confidence: 93%
“…The truthfulness and trustworthiness of our qualitative findings from CHD participants with their discussion of first‐hand and detailed experiences are also verified by the previous studies. Risk perception, which refers to patients’ evaluation of their probability of dangerous events and the harm of the possible event in our study, was reported to enable patients to better understand the importance of reducing their risk for future cardiac events (Figueiras et al, 2017). Consequently, risk perception assists them in engaging in risk‐reducing intentions and behaviours.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, one item estimated absolute CVD risk: "What do you think the risk of your getting any kind of cardiovascular disease within the next 10 years is?" by selecting a number from 1 to 10, with 0 = no risk and 10 = very high risk, a question routinely used in CVD risk perception related studies 16,28 .…”
Section: Methodsmentioning
confidence: 99%
“…These measures were adapted from previous studies on risk perception in non-clinical samples [34]. The participants were asked to rate the perceived individual and compared risk of breast cancer on an 11-point scale ranging from zero (no risk) to ten (high risk).…”
Section: Risk Perceptions (Perceived Individual Risk and Compared Risk)mentioning
confidence: 99%